A call to incorporate a reproductive justice agenda into reproductive health clinical practice and policy - Gilliam, Melissa L.; Neustadt, Amy; Gordon, Rivka (Contraception, 2009)
Keywords: approches et analyses; contraception; discipline; droits des femmes*; intersectionnalité; inégalités; justice reproductive; justice sociale; médecine; ressource en ligne; santé; santé des femmes*; sciences; sciences humaines; sexologie; systèmes d'oppressions; thématiques

Critical intersex - Holmes, Morgan (Ashgate, 2009)
To date, intersex studies has not received the scholarly attention it deserves as research in this area has been centred around certain key questions, scholars and geographical regions. Exploring previously neglected territories, this book broadens the scope of intersex studies, whilst adopting perspectives that turn the gaze of the liberal, humanist, scientific outlook upon itself, in order to reconfigure debates about rights, autonomy and subjectivity, and challenges the accepted paradigms of intersex identity politics. Presenting the latest theoretical and empirical research from an international group of experts, this is a truly interdisciplinary volume containing critical approaches from both the humanities and social sciences. With its contributions to sociology, anthropology, medicine, law, history, cultural studies, psychology and psychoanalysis, Critical Intersex will appeal to scholars and clinical practitioners alike.
Section: 1 vol. (XIV-257 p.) ; 24 cm.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; inégalités; premier cycle; queer; santé; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; violences; violences médicales; études intersexes